2019
DOI: 10.1002/1873-3468.13348
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Megf10/Drpr gain‐of‐function on muscle development in Drosophila

Abstract: Recessive mutations in multiple epidermal growth factor‐like domains 10 (MEGF10) underlie a rare congenital muscle disease known as MEGF10 myopathy. MEGF10 and its Drosophila homolog Draper (Drpr) are transmembrane receptors expressed in muscle and glia. Drpr deficiency is known to result in muscle abnormalities in flies. In the current study, flies that ubiquitously overexpress Drpr, or mouse Megf10, display developmental arrest. The phenotype is reproduced with overexpression in muscle, but not in other tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 87 publications
1
12
0
Order By: Relevance
“…The effects of Ser overexpression at different stages of myogenesis in Drosophila might provide additional insight on the role of this protein, as was shown for Drpr. 63 A marked increase in Jagged2 levels was seen after treating Megf10-deficient myoblasts with a candidate small molecule therapeutic, 62 bolstering our findings in participant muscle tissue and myoblasts.…”
Section: Discussionsupporting
confidence: 53%
“…The effects of Ser overexpression at different stages of myogenesis in Drosophila might provide additional insight on the role of this protein, as was shown for Drpr. 63 A marked increase in Jagged2 levels was seen after treating Megf10-deficient myoblasts with a candidate small molecule therapeutic, 62 bolstering our findings in participant muscle tissue and myoblasts.…”
Section: Discussionsupporting
confidence: 53%
“…In previous studies, we have shown that downregulation of draper (drpr), the Drosophila homolog of Megf10, in quiescent adult muscle precursors (satellite cell-like AMPs) leads to decreased motor activity in corresponding mutant flies [41]. These cells, however, are insensitive to drpr/Megf10 overexpression, which is deleterious later in myogenesis, that is, at the migration/differentiation stages (suggesting that Drpr levels are finely tuned during these steps) [42]. It is well established that drpr plays a crucial role in mediating the migration of glia toward injured neurons [43,44], as well as the migration of immune cells toward tissue wound [45].…”
Section: Discussionmentioning
confidence: 99%
“…Drpr deficiency has been shown to lead to muscle abnormalities in flies. In addition, flies that overexpress mouse MEGF10 or fly Drpr display developmental arrest Frontiers in Physiology frontiersin.org 13 Den Hartog and Asakura 10.3389/fphys.2022.984373 (Draper et al, 2019). In mice, there has been a suggestion for interaction between MEGF10 and the Notch pathway in regulating myogenesis (Table 2; Saha et al, 2017).…”
Section: Other Proteins Associated With the Notch Pathway: Megf10 And...mentioning
confidence: 99%
“…It should be noted that there are several interactions between the Notch pathway and other components in satellite cells, which work together to govern satellite cell proliferation. Multiple EGF-like domains 10 (MEGF10) is a transmembrane receptor expressed in both developing muscle satellite cells and myoblasts, which has exhibited marked similarity to Notch ( Saha et al, 2017 ; Draper et al, 2019 ; Li et al, 2021 ). MEGF10 regulates myogenesis in conjunction with the Notch pathway, and MEGF10 deficiency displays several characteristics similar to Notch deficiency ( Draper et al, 2019 ; Li et al, 2021 ).…”
Section: Other Proteins Associated With the Notch Pathway: Megf10 And...mentioning
confidence: 99%
See 1 more Smart Citation